THE LEGAL POLITICS ASPECT IN THE IMPORTANCE OF CONSUMMATION IN MARRIAGE LAW - Sulistyowati, Sulistyowati; Maharani, Dewi Nadya (Jurnal Pembaharuan Hukum, 2024)
Indonesia is a country of law (rechtsstaat). In terms of regulating its state, Indonesia uses various kinds of laws and regulations. This includes equality between men and women. This gives rise to the term equal protection principle or equality before the law, namely equality and equality of individuals and communities in the eyes of the law. The law relating to marriage and the rights and position of both a wife and a husband in the Civil Code was replaced by Law No. 1 of 1974 on marriage, which has now been revised by the law of the Republic of Indonesia No. 16 of 2019 on amendments to Law No. 1 of 1974 on Marriage (Marriage Law). However, this law has no sanctions if anyone does not comply with it. In this case, we need to amend the Marriage Act. This research is descriptive normative legal research. The theory used theory is the theory of the rule of law, the theory of the purpose of law, and the theory of law enforcement. Data collection techniques are Library Studies (library research).